IMAGING OF POLARIZED LIGHT USING STOKES PARAMETERS (Scientific journal of the Fergana State University, 2023)
In the article, the physical characteristics and analytical method of output of the positions parameters of Stokes describing the flow of polarized light radiation are analyzed in simple and clear way.